LANGUAGE VARIATION IN JAVANESE BETWEEN KERATON and COASTAL COMMUNITY - Agustine, Maghfiroh (LANTERN (Journal on English Language, Culture and Literature), 2013)
The significance of this research is to be a good research that is useful for the researcher, science and society. Therefore, the results of this study are able to enrich the reference of language research, especially concerning with sociolinguistics (Language Change and SocialVariation). In addition, this research hopefully can broaden the knowledge of readers primarily as a reference in research on the discourse of dialogue related to sociolinguistics meaning. At last, this research may god are able to prove to the readers, that javanese language has many variation, as the Javanese community espeialy we have to be proud of this phenomen